2016
DOI: 10.1007/s10797-016-9434-z
|View full text |Cite
|
Sign up to set email alerts
|

Tax evasion in a Cournot oligopoly with endogenous entry

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In addition, the behavior of manufacturing rm evading taxes forces them to transfer some pro t to unskilled labor, in order to gain the support of un-ethic evading-tax behavior, which will further encourage unskilled labor migration. However, manufacturing rms, in order to maximize its pro t, will depress basic salary of unskilled labor even though there is a certain ratio of wage-saving sharing, which is depicted in (12).…”
Section: Analysis Of Pro T Evasion and Wage-saving Sharingmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the behavior of manufacturing rm evading taxes forces them to transfer some pro t to unskilled labor, in order to gain the support of un-ethic evading-tax behavior, which will further encourage unskilled labor migration. However, manufacturing rms, in order to maximize its pro t, will depress basic salary of unskilled labor even though there is a certain ratio of wage-saving sharing, which is depicted in (12).…”
Section: Analysis Of Pro T Evasion and Wage-saving Sharingmentioning
confidence: 99%
“…The reason is that in a collusive tax evasion game with multiple equilibria as shown in Chang and Lai (2004), social norms affect the range of equilibria and act as an equilibrium selection device. Goerke (2017) investigates the impact of pro t tax evasion on rms' output decisions in a Cournot oligopoly setting in which the market structure is determined endogenously. It is shown that tax evasion intensi es market entry and raises aggregate output, while production of each incumbent rm decreases.…”
Section: Introductionmentioning
confidence: 99%